2014
DOI: 10.5194/bg-11-2391-2014
|View full text |Cite
|
Sign up to set email alerts
|

Presence of <i>Prochlorococcus</i> in the aphotic waters of the western Pacific Ocean

Abstract: Prochlorococcus, the smallest but most abundant marine primary producer, plays an important role in carbon cycling of the global ocean. As a phototroph, Prochlorococcus is thought to be confined to the euphotic zone, with commonly observed maximum depths of ∼ 150-200 m, but here we show for the first time the substantial presence of Prochlorococcus populations in the dark ocean ("deep Prochlorococcus" hereafter). Intensive studies at the Luzon Strait in the western Pacific Ocean show that the deep Prochlorococ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 64 publications
(73 reference statements)
2
32
2
Order By: Relevance
“…The typical deep-water OTUs (SAR324 and SAR406) found in the subsurface of the CE indicate an intrusion of deep water in the CE core, consistent with a previous finding from a mode water eddy that also generated upwelling at its core (18). Prochlorococcus plays a key role in the global carbon and energy cycles, and our finding of this bacterium in the mesopelagic layer at the edge of the AE is consistent with the new discovery of Prochlorococcus well below the euphotic layer in the western Pacific Ocean (46). Recent studies indicate that physical-biological interactions have profound implications on the nitrogen fixation in mesoscale structures in the North Pacific Ocean (47).…”
Section: Discussionsupporting
confidence: 91%
“…The typical deep-water OTUs (SAR324 and SAR406) found in the subsurface of the CE indicate an intrusion of deep water in the CE core, consistent with a previous finding from a mode water eddy that also generated upwelling at its core (18). Prochlorococcus plays a key role in the global carbon and energy cycles, and our finding of this bacterium in the mesopelagic layer at the edge of the AE is consistent with the new discovery of Prochlorococcus well below the euphotic layer in the western Pacific Ocean (46). Recent studies indicate that physical-biological interactions have profound implications on the nitrogen fixation in mesoscale structures in the North Pacific Ocean (47).…”
Section: Discussionsupporting
confidence: 91%
“…In the summer SCS picoplankton occupy up to~80% of the total autotrophic biomass in surface waters [Wong et al, 2007], raising the possibility of preferential export of small phytoplankton. In fact, the latest genomic study revealed that substantial amounts of Prochlorococcus populations can be found in the deep waters of the SCS and LS [Jiao et al, 2014], which is supportive of the hypothesis of δ 15 N sink shift by small phytoplankton although the mechanism is not well understood. Flow cytometry-IRMS technique is not yet applied in the SCS to discern isotopic compositions of Prochlorococcus and picoeukaryotes.…”
Section: 1002/2016jg003618mentioning
confidence: 77%
“…Although a high proportion of community variation was depth-related, this might be due to depth being a proxy for various physiochemical factors in oceanic waters. For example, with increasing depth, oceanic waters are prone to become more dense with lower temperature, higher salinity, higher concentrations of dissolved organic matter and lower concentrations of oxygen, each of which is likely to influence microbial trophic function and community structure (Jiao et al, 2013; Pernice et al, 2015; Edgcomb, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For bacterial abundance analysis, which was only conducted for the samples collected in 2014, 1.8 ml seawater sample was pre-filtered onto a 20 μm pore-size membrane and then mixed with ice-cold glutaraldehyde (1% final concentration). Samples were stored at −80°C and were later measured by a flow cytometry (Beckman Coulter, Epics Altra II) (Jiao et al, 2013). Nutrient analysis (ammonia, nitrite, nitrate, dissolved inorganic nitrogen and phosphate) followed Hu et al (2008).…”
Section: Methodsmentioning
confidence: 99%